A randomized controlled trial of structured palliative care versus standard supportive care for patients enrolled in phase 1 clinical trials. (25th May 2021) - Treasure, Michelle; Daly, Barbara; Cao, Shufen; Fu, Pingfu; Hong, Augustine; Weinstein, Elizabeth; Surdam, Jessica; Meropol, Neal J.; Dowlati, Afshin
Abstract: Purpose: Patients enrolled in Phase 1 clinical trials have typically exhausted standard therapies and often are choosing between a clinical trial and hospice care. Significant symptom burden can result in early trial discontinuation and confound trial outcomes. This study aimed to examine differences in study duration, symptom burden, adverse events (AE), and quality of life (QOL) between those receiving structured palliative care versus usual supportive care. Patients and methods: Sixty‐eight patients enrolled in phase 1 clinical trials and 39 of their CGs were randomly assigned to receive structured palliative care or usual supportive care. Patient QOL was measured monthly using the Functional Assessment of Cancer Therapy and Memorial Symptom Assessment Scale. The Quality of Life in Life‐Threatening Illness–Family Care Version and Caregiver Reaction Assessment were used for CGs. AEs and use of palliative care resources were compared between arms. Results: Mean duration of the phase 1 study was 142 days in the palliative care arm versus 116 days in the usual care arm ( p = 0.55). Although not statistically significant, patients in the palliative care arm experienced fewer AEs and better QOL, as did their CGs, compared to those receiving usual care. Conclusions: Phase 1 patients and their CGs have physical and psychosocial needs warranting palliative care services. Results suggest that structured palliative care is associated with the increased duration of the study and improved patient and CG QOL. Abstract : Phase 1 patients and their caregivers have physical and psychosocial needs warranting palliative care services. Providing structured palliative care servies to this population was associated with increased duration on phase 1 study and improved patient and caregiver QOL.